2014
DOI: 10.3390/nu6093431
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sweet Taste in Satiation and Satiety

Abstract: Increased energy consumption, especially increased consumption of sweet energy-dense food, is thought to be one of the main contributors to the escalating rates in overweight individuals and obesity globally. The individual’s ability to detect or sense sweetness in the oral cavity is thought to be one of many factors influencing food acceptance, and therefore, taste may play an essential role in modulating food acceptance and/or energy intake. Emerging evidence now suggests that the sweet taste signaling mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 115 publications
2
41
0
3
Order By: Relevance
“…These studies provide two major outcomes: (1) functional imaging in anaesthetised pigs can be implemented to explore brain responses to different food signals, as in humans; and (2) the brain circuits activated by the perception of food signals are similar to those described in the human (for example, frontostriatal areas, amygdala and insular cortex). Studies in human subjects showed that brain responses to energy-providing sugars and sweeteners are not the same in the reward circuit (for reviews, see Low et al (228) and Ochoa et al (229) ), which resembles the results obtained by Clouard et al (225) in pigs. Clouard et al (225) compared congruent v. dissociated oral and duodenal SUC perception, and found different brain responses in the limbic and reward circuits.…”
Section: Nutrition Research Reviewsmentioning
confidence: 57%
“…These studies provide two major outcomes: (1) functional imaging in anaesthetised pigs can be implemented to explore brain responses to different food signals, as in humans; and (2) the brain circuits activated by the perception of food signals are similar to those described in the human (for example, frontostriatal areas, amygdala and insular cortex). Studies in human subjects showed that brain responses to energy-providing sugars and sweeteners are not the same in the reward circuit (for reviews, see Low et al (228) and Ochoa et al (229) ), which resembles the results obtained by Clouard et al (225) in pigs. Clouard et al (225) compared congruent v. dissociated oral and duodenal SUC perception, and found different brain responses in the limbic and reward circuits.…”
Section: Nutrition Research Reviewsmentioning
confidence: 57%
“…Second, the relationship between peripheral taste sensitivity, appetite, and intake is not fully understood (for review, see [35,36]), though some evidence suggests that prandial orosensory stimulation may contribute to the regulation of food intake. Studies have demonstrated that increased oral processing time (i.e., the length of time the food stimulus remains in the mouth) and increased orosensory exposure per unit of liquid or semisolid food consumption (i.e., sip or bite size) promotes satiation and decreases total intake [3739].…”
Section: Oral Mechanismsmentioning
confidence: 99%
“…44 These compounds could be useful in the prevention of overweightness and obesity in populations which are less sensitive to sweetness, predisposing them to consume more sugar in order to have the same 'taste sensation' as people more sensitive to sweetness. 71 Nowadays low-calorie sweeteners are important tools in DM management, where the dietary adherence is amongst the most difficult cornerstones 72 , especially for children and adolescents with T2DM who suffer from the perceived lack of normality in their diet and consequenlty desire non-recommended sweet foods. 73 Ready-to-consume proprietary foods, high in good quality proteins and fibers, could improve both, the diet of young people, and the diet of T2DM patients.…”
Section: Discussionmentioning
confidence: 99%